Conceptual development of land tenure in Ukraine at the present stage - Tretiak, А. М.; Drugak, V. M. (Землеустрій, кадастр і моніторинг земель, 2011)
We concider the presence of a problem situation and given its characteristics, prognosis of development in the field of land use protection of land. The basic conceptual rules of land management in Ukraine.